An Analysis on Students’ Pronunciation Error in English Diphthong - Umarul Dirgan Ramadhan; Laila Wati; Muhammad Junaidi Marzuki; Usuluddin Usuluddin; Adib Nazri (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
This research analyzes students’ pronunciation errors in English diphthongs in MA NW Teko. The objective was to identify commonly mispronounced errors. The research is descriptive qualitative. The subjects were twelfth grade students at MA NW Teko. Fifteen students were chosen as representatives for analysis. Data was collected from oral tests, interviews, and observations. The data source was a short story called "Sangkuriang". Based on the oral test, students fluently read the story with 14 students in paragraph 1 and 11 students in paragraph 2. In paragraphs 3 and 4, the students read the story with less fluency, with 9 and 12 students respectively. During the interview, students mentioned difficulty in identifying diphthong words due to insufficient vocabulary mastery. In paragraph 1, 8 words were pronounced incorrectly, 13 words in paragraph 2, 10 words in paragraph 3, and 12 words in paragraph 4. However, observation revealed that out of the 5 types of diphthongs given, 14 out of 15 students struggled with pronouncing the diphthong "oʊ", with only 1 student pronouncing it correctly. Therefore, the research results indicate that the errors faced by the students were not significantly different from those who could pronounce correctly.